A Historical and Linguistic Overview of the Maltese Language - Abou El-Ardat, Hadil (International Journal of Language and Literary Studies, 2024)
The Maltese language, a unique member of the Semitic language family, is shaped by strong influences from Malta’s conquerors. What distinguishes the Maltese language from others is Malta’s resilience; despite the various visitors to the island, the language has endured, absorbing influences from each of its visitors and inhabitants in turn. The aim of this paper is to explore the history of Malta and its language, delving into their origin, and how Malta’s visitors, together with Romance languages of Europe, left an impact on the intertwined entity of Malta and its language. This paper analyzes historical sources that show Malta’s rich history and events that have shaped it into the country it is today, tracing the development of Maltese over time. Moreover, it delves into the linguistic aspects of Maltese that include phonology, morphology, syntax, and semantics. A qualitative analysis is applied in the research. The Maltese language is analyzed in regard to Semitic and Romance languages, showing the uniqueness of Maltese and how it is unlike any other language in Europe. This allows the conclusion that Maltese should be studied in more detail, uncovering its roots and linguistic characteristics, as well as evidence of Malta’s turbulent, yet interesting history.